Toward improved education about methicillin-resistant Staphylococcus aureus: A Mental Models Approach to identify the Dutch general public’s beliefs - Verhoeven, Fenne; Karreman, Joyce; Bosma, Anneke; Hendrix, Ron; van Gemert-Pijnen, Lisette (International Journal of Infection Control, 2009)
To identify the relevant beliefs and knowledge (‘mental models’) present among the Dutch general public concerning methicillin-resistant Staphylococcus aureus (MRSA), 17 interviews were conducted followed by a confirmatory questionnaire (n=239). 62% of the public heard of MRSA before via the media. Although the public recognizes well-known risk factors and consequences of MRSA, the public is only slightly aware of its threat to society. Misconceptions exist regarding origin and spread (e.g., that MRSA is caused by overburdened muscles). Besides, knowledge gaps were found concerning prevention, reservoir, and origin (importance of hygiene measures, presence on the skin, MRSA among cattle). These beliefs must be considered by those designing risk communication and guidelines about MRSA for the public.